Analisa Laporan Keuangan Sebagai Prediksi Kebangkrutan Dengan Metode Z-score Pada 3 Jenis Bank di Indonesia - Rizki Sri Lasmini (Universitas Negeri Padang, 2019)
This study aims to analyze the financial statements to predict bankruptcy by theAltman Z-score model. This study will classify 3 banking industry in Indonesia in terms of ownership and will predict their bankrupt. The bank are government banking, national private banking and joint venture banking . This study was conducted to determine the results of financial ratios for 5 years from 2010 to 2014, and to determine the Z-score obtained from the results of these ratios. Based on the Altman's Z-score method, there are 4 financial ratios used for non-manufacturing companies, namely liquidity ratios in the form of Net Working Capital to Total Assets (X1), profitability ratios of Retained Earning to Total Assets (X2) and Earning Before Interest and Tax to total Assets (X3), and capital of Book Value of Equity to Total Liability (X4).